ANALISIS KESULITAN SISWA KELAS IV DALAM MEMBEDAKAN KPK DAN FPB: KAJIAN LITERATUR DAN IMPLIKASI TERHADAP PENGEMBANGAN MEDIA PEMBELAJARAN - Ni Ketut Emik Krusitawati; Ni Luh Putu Aryastiti; Ni Komang Hepi Satyawati; I Made Sujana Adnyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The difficulty of fourth-grade elementary school students in distinguishing Least Common Multiple (LCM) and Greatest Common Factor (GCF) is a widely documented problem that has yet to be examined comprehensively through cross-study synthesis. This study aims to identify and classify the forms of difficulty experienced by fourth-grade students in differentiating LCM and GCF concepts, and to formulate learning media recommendations responsive to the identified difficulty profiles. A systematic literature review method guided by the PRISMA protocol was employed, analyzing 24 articles selected from 187 articles identified through Google Scholar, ERIC, Semantic Scholar, and SINTA databases, published between 2013 and 2024. Data analysis was conducted using thematic content analysis. The findings identified three main clusters of difficulty: conceptual difficulty, characterized by the inability to distinguish the meanings of multiples and factors; procedural difficulty, manifested as errors in applying prime factorization algorithms; and contextual difficulty, reflected in students' failure to identify the relevant concept when solving word problems. These difficulties stem from overly procedure-oriented instruction, limited use of concrete representations, and the absence of contextually meaningful learning media. The study recommends three complementary types of learning media applied sequentially following the concrete-pictorial-abstract approach: manipulative-based enactive media, educational game-based media, and technology-based interactive visual media. These findings carry direct implications for teachers in designing LCM and GCF instruction grounded in conceptual understanding rather than procedural memorization).